1981
DOI: 10.1111/j.1939-0025.1981.tb01416.x
|View full text |Cite
|
Sign up to set email alerts
|

Children: The unintended victims of marital violence.

Abstract: This paper attempts to investigate the effects of wife‐battering on children. Current behavior problems of the children are examined and potential long‐term consequences are evaluated through retrospective examination of the abusive husband. Findings suggest that both present and future behavior may be adversely affected by childhood exposure to domestic violence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
87
1
6

Year Published

1990
1990
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(96 citation statements)
references
References 12 publications
2
87
1
6
Order By: Relevance
“…There is also some support for the hypothesis that children from violent families of origin carry violent and violence-tolerant roles to their adult intimate relationships (Cappell & Heiner, 1990;Rosenbaum & O'Leary, 1981;Widom, 1989). For example, Rosenbaum and O'Leary (1981) reported that the male batterers in their study were much more likely than others to have grown up in homes where adult domestic violence was occurring.…”
Section: Children's Problems Associated With Witnessing Violencementioning
confidence: 67%
See 2 more Smart Citations
“…There is also some support for the hypothesis that children from violent families of origin carry violent and violence-tolerant roles to their adult intimate relationships (Cappell & Heiner, 1990;Rosenbaum & O'Leary, 1981;Widom, 1989). For example, Rosenbaum and O'Leary (1981) reported that the male batterers in their study were much more likely than others to have grown up in homes where adult domestic violence was occurring.…”
Section: Children's Problems Associated With Witnessing Violencementioning
confidence: 67%
“…For example, Rosenbaum and O'Leary (1981) reported that the male batterers in their study were much more likely than others to have grown up in homes where adult domestic violence was occurring. A similar finding is also reported in a study by Barnett, Butler and Ryska (1987).…”
Section: Children's Problems Associated With Witnessing Violencementioning
confidence: 99%
See 1 more Smart Citation
“…The DAS is a widely used, 32-item measure of marital satisfaction. It has demonstrated high internal consistency and has been shown to distinguish between distressed and nondistressed couples and between abusive and discordant, nonabusive couples (Rosenbaum & O'Leary, 1981). DAS scores range from 0 to 151, with scores below 100 typically used to identify marital distress.…”
Section: Methodsmentioning
confidence: 99%
“…L'étude de Hennings, Leintenberg, Coffey, Turner et Bennett (1996) indique que les femmes qui ont été exposées à la violence conjugale durant leur enfance démontrent un niveau plus élevé de détresse psychologique et un niveau moins élevé d'ajustement social. Pour leur part, les conjoints violents sont plus susceptibles d'avoir été témoins ou victimes de violence dans leur famille d'origine (Straus, Gelles et Steinmetz, 1980;Rosenbaum et O'Leary, 1981). L'estimation de la proportion d'hommes abuseurs qui proviennent de familles possédant une histoire de violence oscille entre 50 % (Sonkin, Martin et Walker, 1985) et 80 % (Roy, 1982) selon les études.…”
Section: Les Conséquences De La Violence Conjugale Sur Les Enfantsunclassified